(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This paper titled "Gender Imbalance in Nigerian University System" was carried out to analyze the factors responsible for the gender imbalance in universities in Nigeria. Secondary data were collected from print and online publications. A content analytical approach was employed in the research methodology. The study concluded that poor implementation of gender policies, cultural factors, socio-economic status of parents, traditional beliefs, early marriage, poor funding of female education, poor access to educational opportunities, weak institutions and patriarchal practice are the factors responsible for the gender imbalance in the Nigerian university system. Based on the factors identified, the paper among other recommendations for full implementation of all gender policies in the universities across Nigeria.